2017
DOI: 10.3390/nu9050511
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable and Fruit Intake and Fracture-Related Hospitalisations: A Prospective Study of Older Women

Abstract: The importance of vegetable and fruit intakes for the prevention of fracture in older women is not well understood. Few studies have explored vegetable and fruit intakes separately, or the associations of specific types of vegetables and fruits with fracture hospitalisations. The objective of this study was to examine the associations of vegetable and fruit intakes, separately, and specific types of vegetables and fruits with fracture-related hospitalisations in a prospective cohort of women aged ≥70 years. Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
2
19
0
1
Order By: Relevance
“…This approach assumes that the risk of a fall would have remained the same during the remainder of the follow-up period in those that died and in those that did not. This model was chosen as we have previously demonstrated that fruit and/or vegetable intakes are associated with mortality risk and fractures in this cohort using the same cause-specific approach (31,32) . Falls-related hospitalisation absolute risk difference (ARD) and number need to treat to prevent one fall was calculated between women with high (≥3 serves/d) v. low (<2 serves/d) vegetable intake.…”
Section: Discussionmentioning
confidence: 99%
“…This approach assumes that the risk of a fall would have remained the same during the remainder of the follow-up period in those that died and in those that did not. This model was chosen as we have previously demonstrated that fruit and/or vegetable intakes are associated with mortality risk and fractures in this cohort using the same cause-specific approach (31,32) . Falls-related hospitalisation absolute risk difference (ARD) and number need to treat to prevent one fall was calculated between women with high (≥3 serves/d) v. low (<2 serves/d) vegetable intake.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetables were grouped on the basis of the 2013 Australian Dietary Guidelines 33 and were modified relating to phytochemical constituents, as previously described. 18,34 Vegetable types included cruciferous (cabbage, brussels sprouts, cauliflower, and broccoli), allium (onion, leek, and garlic), yellow/ orange/red (tomato, capsicum, beetroot, carrot, and pumpkin), leafy green (lettuce and other salad greens, celery, silver beet, and spinach), and legumes (peas, green beans, bean sprouts, alfalfa sprouts, baked beans, soy beans, soy bean curd and tofu, and other beans).…”
Section: Vegetable Typesmentioning
confidence: 99%
“…For example, diets rich in vegetables and/or fruit have been inversely associated with sarcopenia [ 11 ]. Previously, we have also demonstrated that higher total vegetable intake is associated with lower fracture risk [ 12 ]. To date, however, the importance of vegetable diversity remains unclear.…”
Section: Introductionmentioning
confidence: 99%